A procedural framework for construction claim in Malaysian construction industry / Nor Azmi Bakhary - Bakhary, Nor Azmi (2019)
The construction industry in Malaysia is large and it involves multi disciplinary participants. There is high frequency of disputes arising from construction contract claims. Even with the most expert understanding of construction contract clauses and the most equitable risk-allocation management, claims will continue to present problems if they are poorly managed in practice. Claims for additional costs and time extensions result from a variety of events occurring during the course of construction. The frequency of claims is unavoidable given the nature of the contracts, their complexity, the number of parties involved, the risk and the pressure of time constraint in the preparation of the contract documents and the realization of the work. The significantly increasing number of construction claims indicates the need for the implementation of an effective construction claim management. This research aims to improve the process of claim in construction industry by developing a framework for the contractors. This research explores the problems related to the process of claim from contractors' and quantity surveyor consultants' point of view by studying common procedure categories, distributed into six stages. The stages are claim identification, claim notifications, claim examination, claim documentation, claim presentation and claim negotiation. In achieving the objectives, research methodologies in form of questionnaire survey, in-depth interview and expert interview were adopted. The questionnaire survey meant to get the general perception from the contractors and the quantity surveyor consultant on the problem statement. Based on the replies, further in depth data collection was conducted in the form of semi-structured interview. Finally, proposed framework was validated by four (4) experts which concluded the triangulation approach. Triangulation approach adopted in this research produces a robust and reliable data. At the end of the research, a construction claim framework was developed to indicate the valuable information requirements and significant issues as the basis to improve the claim process. The findings highlight on the three (3) critical claim stages that need to be focused by the construction industry practitioners. There are claim identification, claim notification and claim documentation. The need for a good documentation and record keeping system with a competent site staff that can recognize a claim during project execution is very critical. Keeping appropriate project information is an essential part of project monitoring and reporting. It also appears that a standard and transparent procedure should be put in place whereby contractors would be able to follow in order to properly prepare the claim. In addition, staff awareness, training in how to document and submit a well-supported claim, and negotiations with clients are becoming a necessity. Competency in handling claims will help the construction industry practitioners to determine what constitutes a good claim, how to identify a potential claim, what are the procedures of notification, what need to be compiled and further to put it all together into a perfect and quality claim. This research has successfully investigated the current practices in the industry in dealing with construction claims, common disputed issues associated with construction claims, and the reasons for the failure of such claims. The strategies towards achieving a successful claim have been identified as being comprised of elements that are essential for inclusion in claims and the initiatives to be taken by the construction industry practitioners to reduce the likelihood of failure of such claims.